Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To find the equation of the quadratic function in both vertex and standard form, given the vertex and a point it passes through, we follow these steps:
1. Vertex Form of the Quadratic Function:
The vertex form of a quadratic function is given by:
[tex]\[ y = a(x - h)^2 + k \][/tex]
Here, [tex]\((h, k)\)[/tex] is the vertex of the parabola. Given the vertex [tex]\((-1, 6)\)[/tex], we can substitute [tex]\(h = -1\)[/tex] and [tex]\(k = 6\)[/tex] into the vertex form:
[tex]\[ y = a(x - (-1))^2 + 6 \][/tex]
Simplifying the expression inside the parentheses, we get:
[tex]\[ y = a(x + 1)^2 + 6 \][/tex]
2. Determine the Value of [tex]\(a\)[/tex]:
We are given a point [tex]\((2, 24)\)[/tex] that the function passes through. Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 24\)[/tex] into the equation:
[tex]\[ 24 = a(2 + 1)^2 + 6 \][/tex]
Solve for [tex]\(a\)[/tex]:
[tex]\[ 24 = a(3)^2 + 6 \][/tex]
[tex]\[ 24 = 9a + 6 \][/tex]
Subtract 6 from both sides:
[tex]\[ 18 = 9a \][/tex]
Divide by 9:
[tex]\[ a = 2 \][/tex]
3. Write the Vertex Form:
Substitute [tex]\(a = 2\)[/tex] back into the vertex form:
[tex]\[ y = 2(x + 1)^2 + 6 \][/tex]
4. Convert to Standard Form:
To find the standard form [tex]\(y = ax^2 + bx + c\)[/tex], expand the vertex form:
[tex]\[ y = 2(x + 1)^2 + 6 \][/tex]
First, expand [tex]\((x + 1)^2\)[/tex]:
[tex]\[ (x + 1)^2 = x^2 + 2x + 1 \][/tex]
Substitute back into the equation:
[tex]\[ y = 2(x^2 + 2x + 1) + 6 \][/tex]
Distribute the 2:
[tex]\[ y = 2x^2 + 4x + 2 + 6 \][/tex]
Combine like terms:
[tex]\[ y = 2x^2 + 4x + 8 \][/tex]
Thus, the equations of the quadratic function are:
- Vertex form: [tex]\(\boxed{y = 2(x + 1)^2 + 6}\)[/tex]
- Standard form: [tex]\(\boxed{y = 2x^2 + 4x + 8}\)[/tex]
1. Vertex Form of the Quadratic Function:
The vertex form of a quadratic function is given by:
[tex]\[ y = a(x - h)^2 + k \][/tex]
Here, [tex]\((h, k)\)[/tex] is the vertex of the parabola. Given the vertex [tex]\((-1, 6)\)[/tex], we can substitute [tex]\(h = -1\)[/tex] and [tex]\(k = 6\)[/tex] into the vertex form:
[tex]\[ y = a(x - (-1))^2 + 6 \][/tex]
Simplifying the expression inside the parentheses, we get:
[tex]\[ y = a(x + 1)^2 + 6 \][/tex]
2. Determine the Value of [tex]\(a\)[/tex]:
We are given a point [tex]\((2, 24)\)[/tex] that the function passes through. Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 24\)[/tex] into the equation:
[tex]\[ 24 = a(2 + 1)^2 + 6 \][/tex]
Solve for [tex]\(a\)[/tex]:
[tex]\[ 24 = a(3)^2 + 6 \][/tex]
[tex]\[ 24 = 9a + 6 \][/tex]
Subtract 6 from both sides:
[tex]\[ 18 = 9a \][/tex]
Divide by 9:
[tex]\[ a = 2 \][/tex]
3. Write the Vertex Form:
Substitute [tex]\(a = 2\)[/tex] back into the vertex form:
[tex]\[ y = 2(x + 1)^2 + 6 \][/tex]
4. Convert to Standard Form:
To find the standard form [tex]\(y = ax^2 + bx + c\)[/tex], expand the vertex form:
[tex]\[ y = 2(x + 1)^2 + 6 \][/tex]
First, expand [tex]\((x + 1)^2\)[/tex]:
[tex]\[ (x + 1)^2 = x^2 + 2x + 1 \][/tex]
Substitute back into the equation:
[tex]\[ y = 2(x^2 + 2x + 1) + 6 \][/tex]
Distribute the 2:
[tex]\[ y = 2x^2 + 4x + 2 + 6 \][/tex]
Combine like terms:
[tex]\[ y = 2x^2 + 4x + 8 \][/tex]
Thus, the equations of the quadratic function are:
- Vertex form: [tex]\(\boxed{y = 2(x + 1)^2 + 6}\)[/tex]
- Standard form: [tex]\(\boxed{y = 2x^2 + 4x + 8}\)[/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.